Karakterisktik Faktor Risiko Hipertensi di Makassar Tahun 2017 - Nurhikmawati Nurhikmawati; Syatirah Rizky Ananda; Hasta Handayani Idrus; Wisudawan Wisudawan (Indonesian Journal of Health, 2020)
Hypertension is a manifestation of hemodynamic imbalance disorders of the cardiovascular system, which is the pathophysiology is multi-factor, so it cannot be explained by only one single mechanism. According to the American Heart Association (AHA) 2017, hypertension is a silent killer where symptoms can vary from person to person and the symptoms almost similar with other disease. This study aims to determine the characteristics of the risk factors on hypertension in Makassar in 2017. This study used a descriptive study. The samples were all hypertensive patients who were admitted to the Puskesmas Tabaringan, Jumpandang Baru, Layang, Andalas, Makkasau, Maccini Sawah, Mamajang, Pertiwi, Jongaya, Kassi-kassi, Batua, Tamangapa, Sudiang, Tamalanrea, Makassar from 1 January 2017 to 31 December 2017 as many as 1,528 who met the inclusion and exclusion criteria. The sampling technique used was accidental sampling. From 1,528 research subjects, it was found that the most were aged> 50 years as many as 872 people (57.05), with the most sex are female about 956 people (62.57%). Subjects who had a family history of hypertension were 756 people (49.47%). Most jobs were in the very heavy category about 656 people (42.94%). In addition, 875 people (57.27%) rarely consume salt, and 844 people (55.23%) consume more foods containing fat. In this sample, it was also found that most hypertensive patients were included in the passive smoking category as many as 1,002 people (65.58%). From the lifestyles who have hypertension, there are more who never consume alcohol as many as 1,478 people (96.72%). Subjects who experienced hypertension and were obese were 861 people (56.35%), and sample who rarely exercised were 1,104 people (72.25%). In addition, 877 subjects who had hypertension were found to have never experienced mendengkur (57.4%). Most people with hypertension in Makassar are aged> 50 years, women, do not have a family history of hypertension, work is classified as very heavy category, rarely consume salt, often consume fat, smoke passive, never consume alcohol, obesity, rarely exercise, and never experiencing snoring.